OPTIMIZING THE ALLOCATION OF RESOURCES TO ENSURE TRANSPORTATION SERVICE BY RAIL - Kuleshov, V. M.; Dotsenko, Yu. V. (Science and Transport Progress, 2006)
The problems of railway operation in conditions of developing market of transport products and services have been considered. A mathematical model of distribution of resources on the testing area for ensuring the traffic service has been provided. A conclusion has been made about practical application of this model into cooperated automated workplaces of operative staff to ensure realization of the necessary level of service.